Causative Agents of Vaginitis in Women of Kerman Province, Iran - Mehdi Borhani Zarandi; Saeid Reza Nourollahi Fard; Karim Parastouei; Amin Ahmadi (Pasteur Institute of Iran, 2019)
Introduction: Trichomoniasis is a protozoan infection of women that is transmitted via sexual intercourse. The present study was carried out to detect the prevalence of Trichomonas vaginalis and other vaginitis agents in women referred to Kerman health care centers. Methods: The vaginal discharges of 3988 females were examined by microscopy for T. vaginalis infection as well as bacterial and fungal infections from April 2016 to March 2017. Results: The prevalence rates of T. vaginalis, bacteria, and yeast were 0.2%, 27.3%, and 9.2% respectively. The highest rate of T. vaginalis infection among women belonged to the age group 41-50 (P<0.05). Our results showed Escherichia coli and Klebsiella in women with bacterial infections. Conclusion: The results indicated that the prevalence of T. vaginalis in patients of this area was low, and other causes of vaginitis such as bacterial and fungal infections should be more considered.